INTEGRATING ERP AND E-BUSINESS: WITH TOP MANAGEMENT LEADERSHIP STYLE - Miftah Maulana (Prosiding Amal Insani Foundation, 2022)
Process improvement in the production system is a necessity for each company to enable better monitoring and control, as well as to provide all important timing information for the decision-making process, to improve all processes and simultaneously control all elements of the process. Some of the systems that provide process monitoring are ERP Enterprise Resource Planning Systems and leadership styles but they often have an impact on ERP Integration. We find that transformational leadership and transactional leadership offer new perspectives on integration theory and provide guidance for top management to exercise specific leadership behaviors to achieve long-term ERP integration and ERP success.